تأثير تقلبات أسعار النفط على الأسواق المالية الناشئة دراسة حالة السوق المالي السعودي والتركي (2008– 2024) - ولابي رحمة; الصالحة شكيمة (جامعة الوادي University of Eloued, 2025)
This study aimed to analyze the relationship between oil prices and stock markets in a dual economic context encompassing the Kingdom of Saudi Arabia as an oil-exporting country and the Republic of Turkey as an energy-importing country, over the period 2008–2024. The aim was to determine the nature of this relationship and its differences between the two economic environments. Based on econometric data analysis, the study concluded that the relationship between oil prices and stock markets is not uniform or fixed, but rather varies depending on the nature and structure of the economy. It was found that the Saudi economy, due to its rentier nature and heavy dependence on oil, exhibits greater sensitivity to price fluctuations, especially in the short term. Contrary to expectations, the Turkish market also showed a positive relationship with oil prices, which may be attributed to indirect factors such as inflation and global demand. This highlights the importance of economic diversification in exporting countries and the adoption of flexible investment policies in importing countries. It also highlights the need to develop explanatory models to include additional macro-variables for a deeper understanding of the dynamic relationship between oil prices and financial markets هدفت هذه الدراسة إلى تحليل العلاقة بين أسعار النفط وأسواق الأسهم في سياق اقتصادي مزدوج يشمل المملكة العربية السعودية بوصفها دولة مصدّرة للنفط، وجمهورية تركيا كدولة مستوردة للطاقة، وذلك خلال الفترة 2008–2024، بغرض تحديد طبيعة هذا الارتباط واختلافه بين البيئتين الاقتصاديتين. وفي ضوء التحليل القياسي للبيانات، خلصت الدراسة إلى أن العلاقة بين أسعار النفط وأسواق الأسهم ليست موحدة أو ثابتة، بل تختلف باختلاف طبيعة الاقتصاد وهيكليته. فقد تبين أن الاقتصاد السعودي، لطبيعته الريعية واعتماده الكبير على النفط، يظهر حساسية أكبر لتقلبات الأسعار، خاصة على المدى القصير، في حين أظهرت السوق التركية، خلافًا للتوقعات، علاقة طردية أيضًا بأسعار النفط، ما قد يُعزى لعوامل غير مباشرة. وبذلك تبرز أهمية تنويع الاقتصاد في الدول المصدّرة، واعتماد سياسات استثمارية مرنة في الدول المستوردة، فضلًا عن ضرورة تطوير النماذج التفسيرية لتشمل متغيرات كلية إضافية لفهم أعمق للعلاقة الديناميكية بين أسعار النفط والأسواق المالية.
ماسترالعلوم الإقتصادية
Keywords: oil prices – stock prices – emerging financial markets – saudi economy – turkish economy – ardl model; أسعار النفط; أسعار الأسهم; الأسواق المالية الناشئة; الاقتصاد التركي; الاقتصاد السعودي; نموذج ARDL